Immediate delivery compared with expectant management after preterm pre-labour rupture of the membranes close to term (PPROMT trial): a randomised controlled trial - Morris, Jonathan M.; Roberts, Christine L.; Bowen, Jennifer R.; Patterson, Jillian A.; Bond, Diana M.; Algert, Charles S.; Thornton, Jim; Crowther, Caroline A. (Elsevier, 2016)
Background